Head‐to‐tail cyclization of side chain‐protected linear peptides to recapitulate genetically‐encoded cyclized peptides. Issue 3 (6th January 2022) - Bouayad‐Gervais, Samir; St‐Cyr, Daniel J.; Courcelles, Mathieu; Bonneil, Éric; Gohard, Florence H.; Thibault, Pierre; Earnshaw, William C.; Tyers, Mike
Abstract: Genetically‐encoded cyclic peptide libraries allow rapid in vivo screens for inhibitors of any target protein of interest. In particular, the Split Intein Circular Ligation of Protein and Peptides (SICLOPPS) system exploits spontaneous protein splicing of inteins to produce intracellular cyclic peptides. A previous SICLOPPS screen against Aurora B kinase, which plays a critical role during chromosome segregation, identified several candidate inhibitors that we sought to recapitulate by chemical synthesis. We describe the syntheses of cyclic peptide hits and analogs via solution‐phase macrocyclization of side chain‐protected linear peptides obtained from standard solid‐phase peptide synthesis. Cyclic peptide targets, including cyclo‐[CTWAR], were designed to match both the variable portions and conserved cysteine residue of their genetically‐encoded counterparts. Synthetic products were characterized by tandem high‐resolution mass spectrometry to analyze a combination of exact mass, isotopic pattern, and collisional dissociation‐induced fragmentation pattern. The latter analyses facilitated the distinction between targets and oligomeric side products, and served to confirm peptidic sequences in a manner that can be readily extended to analyses of complex biological samples. This alternative chemical synthesis approach for cyclic peptides allows cost‐effective validation and facile chemical elaboration of hit candidates from SICLOPPS screens. Abstract :